Pressure Broadening of Some He I Lines. (7th September 2009) - Omar, Banaz
Abstract : Quantum statistical approach is adopted for calculating the spectral line shapes of neutral helium in dense plasmas. Stark broadening of isolated He I lines 5048 Å (2 1 P − 4 1 S ), 3889 Å (2 3 S − 3 3 P ), and 3188Å (2 3 S − 4 3 P ) is presented. Based on thermodynamic Green's function, the electronic contribution to the shift and width is considered. The participation of ions to the line broadening is treated in a quasistatic approximation, by taking both quadratic Stark effect and quadrupole interaction into account. The calculated shifts and widths are compared with existing data.